The health needs of the physically handicapped students in the first year of four public secondary schools in Manila - Calica, Hilaria (Rimorin) 1931- (s.n.], 1970)
The main purpose of the study is to determine the health needs of the physically handicapped first year students of four public secondary schools in Manila. The research seeks to identify the prevailing health needs in each type of physical handicap, the health need variations with the kind of physical handicaps of the students, and the variations of health needs with the sex of physically handicapped students. The author hopes that the results of the study be utilized by teachers and curriculum makers as a guide in selecting learning experiences appropriate for the needs of the group.